The first autochthonous case of diphyllobothriosis, caused by broad fish tapeworm (Dibothriocephalus latus), in the Czech Republic - Scholz, T; Kuchta, R; Brabec, J; Pavelková, V; Lapáčková, Z (Epidemiologie, mikrobiologie, imunologie, 2025)
Diphyllobothriosis is a parasitic infection of humans caused by the broad fish tapeworm (Dibothriocephalus latus; synonym Diphyllobothrium latum). This disease is widespread in the Northern Hemisphere including Europe. Popular sport fish such as perch (Perca fluviatilis) and pike (Esox lucius) are the source of human infection. Here we document the first autochthonous case of diphyllobothriosis linked to the consumption of raw pike roe (caviar) originating from a popular tourist destination in South Bohemia. This is probably a recent introduction of the parasite into the Lipno Reservoir, which may represent a new focus of diphyllobothriosis, a zoonotic, fish-borne disease.
Keywords: broad fish tapeworm; Animals; mužské pohlaví; Central Europe; zvířata; Diphyllobothriasis; Humans; pike; zoonosis; difylobotriáza; Czech Republic; Lipno Reservoir; roe; Freshwater fish; lidé; Male; Diphyllobothrium; Česká republika